Partisipasi Masyarakat Dalam Manajemen Rehabilitasi dan Rekonstruksi Pasca Bencana Tsunami Tahun 2018 di Kabupaten Pandeglang - Nur Ikhsani Rahmatika; Sobar Sutisna; Arief Budiarto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Participation from all parties is important in post-disaster rehabilitation and reconstruction because it is the most complex activity in disaster management from the planning process, funding, and implementation. A Tsunami that struck Sunda strait in December 2018 caused a great loss and immediate response is necessary. The delay of rehabilitation and reconstructions affected the stability of national security. Therefore, all parties need to take part in post-tsunami recovery so that the disaster recovery process implemented effectively and efficiently. The purpose of this study was to analyze the participation of society in the post-tsunami rehabilitation and reconstruction management in Pandeglang district, coordination networking, and contributions to national security. The qualitative method is used in this research from the primary and secondary databases. For the purposes of this study, the primary data were gathered through face-to-face interviews from the subjects of research who were chosen based on purposive sampling and snowball methods. The data analyzed qualitatively and simulation by UCINET 6 is used for coordination networking. The result shows that all parties had taken part in the Pandeglang post-tsunami recovery management from the planning process, implementation, monitoring, and evaluations. The level and form of community participation are diverse.